“I Want to Be Stepping in More” - Professional Online Forum Moderators' Experiences of Supporting Individuals in a Suicide Crisis - Perry, Amanda; Lamont-Mills, Andrea; Preez, Jan du; Plessis, Carol du (Frontiers in Psychiatry, 2022)
Introduction Individuals experiencing suicidal crises increasingly turn to online mental health forums for support. Support can come from peers but also from online moderators, many of whom are trained health professionals. Much is known about users' forum experiences; however, the experiences of professional moderators who work to keep users safe has been overlooked. The beneficial nature of online forums cannot be fully realized until there is a clearer understanding of both parties' participation. This study explored the experiences of professional online forum moderators engaged in suicide prevention. Materials and Methods A purposive sample of professionally qualified moderators was recruited from three online mental health organizations. In-depth semi-structured, video-recorded interviews were conducted with 15 moderators (3 male, 12 female), to explore their experiences and perceptions of working in online suicide prevention spaces. Data was analyzed using inductive thematic analysis. Results Five themes were identified related to the experiences and challenges for moderators. These were the sense of the unknown, the scope of the role, limitations of the written word, volume of tasks, and balancing individual vs. community needs. Discussion Findings indicate that the professionally qualified moderator role is complex and multifaceted, with organizations failing to recognize these aspects. Organizations restrict moderators from using their full therapeutic skill set, limiting them to only identifying and re-directing at-risk users to crisis services. The benefits of moderated online forums could be enhanced by allowing moderators to use more of their skills. To facilitate this, in-situ research is needed that examines how moderators use their skills to identify at-risk users.